Enhanced Oxidative Hydrogen Peroxide Production on Conducting Glass Anodes Modified with Metal Oxides. Issue 18 (14th November 2016) - Fuku, Kojiro; Miyase, Yuta; Miseki, Yugo; Gunji, Takahiro; Sayama, Kazuhiro
Abstract: Surface modification of conductive oxide glass (F‐SnO2 : FTO) anode substrates using 10 oxides was investigated for efficiently producing oxidative hydrogen peroxide (H2 O2 ) from water with hydrogen (H2 ) production at a Pt cathode. Bismuth vanadate (BiVO4 ) or titanium oxide modification significantly facilitated oxidative H2 O2 production in an aqueous solution of bicarbonate (HCO3 − ) on the anode substrate in the dark. The BiVO4 ‐supported FTO anode (BiVO4 /FTO) achieved not only approximately twice the H2 O2 generation performance compared with a bare FTO substrate but also high H2 O2 accumulation, and the maximum selectivity (η(H2 O2 )) and accumulation reached ca . 35 % and 5 mM, respectively. Abstract : BiVO4 acted as an excellent surface‐modification agent on an FTO anode for the design of an electrochemical water splitting system that simultaneously produces and accumulates hydrogen peroxide (H2 O2 ) and hydrogen (H2 ), using the catalytic properties of BiVO4 for generating H2 O2 from H2 O in aqueous solution of bicarbonate (HCO3 − ).